Risk Analysis in Business Plan - Roháčková, Sabina; Hnilica, Jiří, 1976-; Cimický, Jan; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2009)
This paper aims to deliver insights into the field of structuring a business plan for start-up companies and implementing an efficient risk analysis in the course of business planning. In order to achieve this goal, this thesis challenges the theory with practice to equally reflect both perspectives. The theoretical part first reviews the literature dealing with business plan outlines and, then, presents the author's own systematic methodology to the risk analysis in business planning. The empirical part provides a real-life example of a structured business plan where the risk analysis concept designed by the author is applied. The conclusions from this paper are the following: The business plan outline is situational and cannot be standardized to one fixed pattern or framework. The risk analysis in a business plan increases its transparency and credibility and, therefore, it should be considered for its inherent part. The application of the risk analysis across the business plan shall follow a systematic approach, which is an adapted version of official risk management standards. In this paper, the author's own adapted framework of the risk analysis in the context of business planning is elaborated and applied to the real-life business plan.
Vedoucí práce: Jiří Hnilica
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Způsob přístupu: Internet
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2010
Rok obhajoby 2010
Keywords: international Management [obor dipl. práce]; diplomové práce; master's theses